Antioxidant and Antifungal Activity of Jeringau (Acorus calamus L.) Extract In Some Organic Solvents In Vitro - Muchtaromah, Bayyinatul; Ahmad, Mujahidin; Hasan, M. Nur; Wahyudi, Didik (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2017)
Candidiasis is one disease that has experienced by 75% of women in Indonesia caused by fungal infection,Candida albicans. Candidiasis can cause serious complications such as infertility. One of the best known ingredients to cure infertility problems is jeringau rhizome (Acoruscalamus L.). This research is the first step to process for Â standardization and scientification of jeringau rizhome as one of the basic ingredients of Madura traditional medicine, jamu